Design Of Multi-Modulation Baseband Modulator And Demodulator For Software Defined Radio - Chye, Yin Hui (2011)
In contrast to hardware-based radio that only delivers single communication service using particular standard, the software defined radio (SDR) provides a highly reconfigurable platform to integrate various functions for multi-modulation, multiband and multi-standard wireless communication systems. However, this project is only based on multi-modulation SDR, such as 4-PAM, BPSK, QPSK and 16-QAM.The configurable multi-modulation baseband modulator (MMBM) and demodulator (MMBD) are designed using digital signal processing (DSP) algorithms based on common features shared by single-modulation structures, and then implemented into Xilinx Virtex-4 FPGA. Comparing the real-time and simulation results shows that the timings are equivalent, and the sign and magnitude changes are significant.